PENGELOLAAN FULL DAY SCHOOL STUDI SITUS SMP ISLAM TERPADU HARAPAN BUNDA SEMARANG - Bulqis, Siti (2011)
The pupose of this study are: 1) to know the characteristics of school layout 2) to know the characteristics of students activites, and 3) to know the characteristics of learning process interactions. The object of study is Integrated Islamic Junior High School Harapan Bunda Semarang). This study is a qualitative research by ethnography design and it is limited to the head master, vice head master, teachers of class representatives, teachers, administrative staff, and the students. Data collected by observation, indepth interview, and documentation. Data analysis technique is analysis of the site. The first finding showed that the schools occupies three floors building, and all of the required facilities are quite available, that are learning rooms, library, sport center, mosque, etc. As an islamic school, the layout characteristic of the class is differentiated based on the sex. The using of class rooms is moving class system, supported by competency. The second finding showed that the school implements full day school system concistenly, from 07.00 until 15.30 pm. The activities are tasmi' AlQuran, reading Asmsul Husna, praying before lesson, and than learning activitiy, mentoring, and also shalat dzuhur and shalat ashar on congregation with all of the members of th school. The third finding showed that learning interaction consists of interaction between student and teacher, student and student, student and learning media, interaction between the school and the student's parents which are mutaba'ah yaumiyah and monthly meeting, and also interaction between the school and society by out of school education and social service.